Population dynamics of Eye-Spotted Barb (Hampala dispar: Cyprinidae) in Huai Kho Reservoir, Na Chueak District, Maha Sarakham Province, Thailand - SATIENPONG KHOWHIT; TAWATCHAI TANEE; DOONNAPUT KHOWHIT; NATAPOL PUMIPUNTU; NARONGRIT MUAGMAI; PANNAWADEE MUSIRI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Khowhit S, Tanee T, Khowhit D, Pumipuntu N, Muagmai N, Musiri P. 2024. Population dynamics of Eye-Spotted Barb (Hampala dispar: Cyprinidae) in Huai Kho Reservoir, Na Chueak District, Maha Sarakham Province, Thailand. Biodiversitas 25: 3095-3104. The study aims to analyze the population dynamics of the Eye-Spotted Barb (Hampala dispar (Smith, 1934)) in Huai Kao Reservoir, Thailand, focusing on age, growth, mortality, and other notable population characteristics. Fish specimens were collected monthly from January to December 2022 at six locations, selected based on information provided by local fishermen, using experimental gillnet fishing. A total of 1,060 individuals were analyzed with the FiSAT II program (FAO-ICLARM Stock Assessment Tools) to estimate population parameters. The study observed fish lengths ranging from 89 to 235 mm, with an average length of 148.47±25.83 mm. Fish weights varied between 13.0 and 191.0 g, averaging 46.04±27.48 g. The length-weight relationship was described by the equation LWR = 0.0000135L4.86723 (r² = 0.98), modeled the length-weight relationship, indicating a positive allometric growth with an allometric coefficient (b) greater than 3.00 for the H. dispar population. Key growth parameters included a growth performance index (?) of 4.11 years?¹, an asymptotic length (L?) of 246.75 mm, and a growth coefficient (K) of 0.21 years?¹. The probabilities of capture at various lengths were L25% = 108.99 mm, L50% = 186.52 mm, and L75% = 191.44 mm. Instantaneous mortality rates were calculated as M = 0.37 year?¹ for natural mortality, F = 0.60 year?¹ for fishing mortality, and Z = 0.97 year?¹ for total mortality. Recruitment was continuous throughout the year, peaking between February and June, with rates ranging from 11.19% to 16.41%. Virtual Population Analysis (VPA) showed that most H. dispar were caught at lengths between 130 mm and 160 mm, with maximum Fishing mortality (F) occurring at a mid-length of 220 mm, where F reached 0.60 year?¹. An estimated total steady-state biomass of 8.46 tons was found, and with a maximum exploitation rate (Emax) of 0.954 and Exploitation rate (E) of 0.62, it indicates high fishing pressure (E>0.50) on H. dispar in the Huai Kho Reservoir, Thailand. Thus, the environmental conditions of Huai Kho Reservoir are favorable for the growth of the H. dispar and can support an increase in their population.